MIRDC TBI Scenarios for future strategic development plans - Millo, Ma. Girlie M. (University of the Philippines Diliman, 2010)
Business Incubators, in general, aim, to help the growth and survival of new companies through support for help. The Metals Industry Research and Development Center (MIRDC), an agency under the Department of Science and Technology (DOST), established its own TBI Program and opened its facilities to fledging enterprises engaged in technology-based, metalworking-related activities. After nearly two decades, the TBI program operation remains relatively the same-a landlord-tenant scheme. There were no in-depth assessments of the performance of the MIRDC-TBI based on best practices. This study utilized information and divergent views and perspectives to bring better understanding on the issues that will help the Center achieve its incubation objectives. The output of the study which consisted of three (3) future scenarios can be utilized as start-up points in the formulation of strategic plans of the Center, in order to improve the MIRDC TBI performance, attribute by attribute. The APEC-based Ten Steps of the Scenario Planning, which was the main exercise in the subject, TM 298 Special Topic Elective- Technology Foresight and Foresight Analysis, was used as the main framework in this study. Business incubation practices from China, Japan and the Philippines, as well as the best business incubation practices studies were utilized as part of the environmental scanning step. The developed scenarios, Scenario 1 : "Business as Usual, the Usual Business", Scenario 2 : "Strength in Numbers" and Scenario 3 : "All the Works", describes three plausible ways on how TBI program could be managed a decade from today. Scenario 1 depicts the situation of the TBI should nothing will be done to improve its operations. Scenario 2 shows how the use of available resources improves the services of the MIRDC TBI. Scenario 3 describes what might happen should MIRDC TBI incorporate the best practices in business incubation in its management and operation. Details of these scenarios can be found in the latter part of this study. The developed scenarios are only the first step. Its effectivity can only be fully realized if it will be communicated, explored and used.